Antibacterial Activity Test of Ethanol Extract, n-Hexane and Ethyl Acetate Fractions of Cardamom Fruit (Amomum cardamomum Soland. Ex Maton Benth) - Nada, Dina Qatrun; Mambang, D Elysa Putri; Nasution, M. Amin; Ridwanto, Ridwanto (Indonesian Journal of Science and Pharmacy, 2025)
Bacterial infection is a global health problem that requires special attention, especially due to increasing resistance to antibiotics. This study aims to determine the antibacterial activity of ethanol extract, n-hexane fraction and ethyl acetate fraction of cardamom fruit (Amomum cardamomum Soland. Ex Maton Benth) against Streptococcus pyogenes and Pseudomonas aeruginosa bacteria. The extraction was done by percolation using 96% ethanol, followed by fractionation using n-hexane and ethyl acetate solvents. Phytochemical screening tests showed the presence of alkaloid, flavonoid, tannin, and saponin compounds known to have antibacterial activity. Antibacterial activity test was conducted using disc diffusion method with five concentrations (10%-50%). The results showed that the ethyl acetate fraction had the greatest inhibition, with the highest inhibition zone against Streptococcus pyogenes of 14.1 mm and Pseudomonas aeruginosa of 16.8 mm at 50% concentration. Inhibition increased with increasing concentration. The ethyl acetate fraction proved to be the most effective because it contains semipolar compounds that are able to penetrate the bacterial cell wall. This study supports the potential of cardamom fruit as an alternative natural antibacterial agent.